Estado situacional e identificación de oportunidades y su relación con las prácticas de eco eficiencia en el Instituto Nacional de Innovación Agraria E.E.A. “San Roque” San Juan Maynas 2023 - Saenz Peña Macedo, Jesus Martin (2025)
The general objective of this research was to evaluate the current situation, identify opportunities for improvement, and promote eco-efficiency practices in the administrative areas of the National Institute of Agricultural Innovation (INIA), specifically at the San Roque Experimental Station in San Juan, Maynas, during 2023. The study was quantitative, descriptive, and non- experimental in design. The target population of the study was the administrative staff of said institution, and the sample consisted of 50 workers. Inclusion and exclusion criteria were considered; the techniques were documentary review and surveys, and the instrument was a questionnaire validated by the Ministry of Agriculture, Livestock, and Livestock (MINAM). The data were analyzed, processed, and tabulated using SPSS v27 and Python v3.11.2. The results indicate variability in energy consumption at INIA San Roque, revealing clear opportunities for improvement during the last quarter of the year. Furthermore, a 21.3% increase in diesel consumption in the last quarter reveals an operational dependence on heavy machinery and poor energy use planning. INIA San Roque's administrative staff applies certain basic eco-efficiency practices, such as turning off lighting, reducing paper use, and partially reusing materials. However, these actions lack continuity, monitoring, and institutional support, limiting the sustainability of these good practices, which currently depend more on individual initiative than on organizational policy.